Islam and technological development in Malaysia’s health care: An Islamic legal basis analysis of dental materials used in periodontal therapy - Nadia Halib; Wan Abdul Fattah Ismail; Haslinda Ramli; Nur Akilah Abdul Ghaffar; Shofian Ahmad; Nik Salida Suhaila Nik Saleh (Universiti Kebangsaan Malaysia, 2024)
Non-Indexed Publication